Co-expression of Arabidopsis NHX1 and bar Improves the Tolerance to Salinity, Oxidative Stress, and Herbicide in Transgenic Mungbean - Kumar, Sanjeev; Kalita, Angkana; Srivastava, Richa; Sahoo, Lingaraj (Frontiers in Plant Science, 2017)
Mungbean is an important pulse crop extensively cultivated in Southeast Asia for supply of easily digestible protein. Salinity severely limits the growth and productivity of mungbean, and weeding poses nutritional and disease constraints to mungbean cultivation. To pyramid both salt tolerance and protection against herbicide in mungbean, the AtNHX1 encoding tonoplast Na+/H+ antiporter from Arabidopsis, and bar gene associated with herbicide resistance were co-expressed through Agrobacterium-mediated transformation. Stress inducible expression of AtNHX1 significantly improved tolerance under salt stress to ionic, osmotic and oxidative stresses in transgenic mungbean plants compared to the wild type (WT) plants, whereas constitutive expression of bar provided resistance to herbicide. Compared to WT, transgenic mungbean plants grew better with higher plant height, foliage, dry mass and seed yield under high salt stress (200 mM NaCl) in the greenhouse. The improved performance of transgenic plants under salt stress was associated with enhanced sequestration of Na+ in roots by vacuolar Na+/H+ antiporter and limited transport of toxic Na+ to shoots, possibly by restricting Na+ influx into shoots. Transgenic plants showed better intracellular ion homeostasis, osmoregulation, reduced cell membrane damage, improved photosynthetic capacity and transpiration rate as compared to WT when subjected to salt stress. Reduction in hydrogen peroxide and oxygen radical production indicated enhanced protection of transgenic plants to both salt- and methyl vialogen (MV) - induced oxidative stress. This study laid a firm foundation for improving mungbean yield in saline lands in Southeast Asia.